Streaming and Studentsâ Self-Esteem: A Qualitative Study on Teachersâ Correspondence Bias - Chin Sook Fui, Prihadi Kususanto (Universitas Ahmad Dahlan, 2012)
AbstractThis study was aimed to investigate the effect of studentsâ streaming practice in Malaysian secondary on studentsâ self-esteem through teachersâ expectancy.Â 17 teachers and 20 students from art and science streams of secondary schools in Penang, Malaysia were participated in this study. Unstructured interviews were used on teachers to collect the qualitative data of teachersâ expectancy. The participating students were from the fourth year of secondary school in Malaysian school system (between 16-17 years old, 10 from science stream and 10 from arts stream) were interviewed in order to collect the qualitative data of teachersâ perceived behavior and self-esteem. Result of this study shown that teachers expected science stream students to have good academic performance but expected arts stream students to be involved in disciplinary problems. Furthermore, science stream students perceived that their teachers were academically supportive but arts stream students perceived that their teachers were focusing on controlling their behavior. On the other hand, findings of this study also revealed that science stream students possed higher level of self-esteem than arts stream students. Accordingly, it was indicated that teachersâ perceived behavior and teachersâ expectancy are correlated to one another, and teachersâ perceived behavior predicts studentsâ self-esteem.Keywords:Â Streaming, studentsâ self-esteem, teachersâ expectancy, science stream, arts stream, supportive, controlling.